Experimental study of in-plane mechanical performance of carbon/glass hybrid woven composite at different strain rates. Issue 6 (1st November 2016) - Zhu, Ping; Lu, Jiahai; Ji, Qinghui; Cheng, Zhang
ABSTRACT: Woven composite has been increasingly employed in engineering applications undergoing complex loading conditions. For effective use of composite materials, it is essential to fully understand the mechanical behaviour of composite at different strain rates. In the present study, both in-plane tensile and compressive mechanical properties of a carbon/glass hybrid plain weave composite were experimentally investigated over the strain rate range from 0.001 to 1000 s −1 . High strain rate tests were carried out using Split Hopkinson Pressure and Split Tensile Bar apparatuses, respectively. Experiments were performed at the axial direction of 0° and 90°, and the off-axial direction of 45° considering the tension/compression asymmetry and anisotropy characteristic. The results indicated that the in-plane mechanical performance was strain rate sensitive under both tensile and compressive loadings. Highly direction-dependent and tension/compression asymmetric characteristic was observed under quasi-static and high strain rate loadings. The elastic modulus showed no strain rate sensitivity for the 0° axial tension. However, for other loading conditions, the elastic modulus was enhanced by 1.7–7.2 times under high strain rate loading. The strength was increased by 1.2–2.5 times at 1000 s −1 compared with that under quasi-static loading for different loading directions. For higher strain rate sensitivity under compression than tension, the asymmetry was less obvious with the increase of strain rate. Two phenomenological models were proposed to quantitatively fit the relationship between the strength property and strain rate, which showed great consistency between the experimental and fitted results.